KLİNİSYEN VETERİNER HEKİMLİĞİNDE ETİK KARAR VERME SÜRECİ ÜZERİNE UYGULAMALI BİR ARAŞTIRMA - VURAL, TUNCAY (Fırat Üniveristesi, 2024)
Etik karar verme süreci, veteriner hekimlerin etik problemle karşılaşmasıyla başlayan, çok boyutlu ve karmaşık bir süreçtir. Son yıllarda artan teknolojiyle birlikte yaşanan etik problemlerdeki artış ve mesleğin doğasından gelen etik sorunların, veteriner hekimlerin ruh sağlığı ve mesleğin saygınlığı üzerinde olumsuz etkileri bilinmektedir. Bu durumun temel nedeni, veteriner hekimlerin mesleki uygulamalarda karşılaştığı vakalarda genel kabul görmüş teşhis tedavi standartları olmasına rağmen, etik vakalarda benzer bir kabulün olmamasıdır. Bu çalışma, klinisyen veteriner hekimlerin mesleki uygulamalar sırasında karşılaştıkları etik problemlerin çözümüne ilişkin karar verme sürecinde nasıl bir yol izlediklerini anlama; bu süreçte etkili olan faktörleri ortaya koyma; etik problemlerin çözümü aşamasında ahlâkî konfor düzeyini belirlemede kullanılabilecek, güvenilir ve geçerli bir ölçme aracı geliştirme amacıyla yapılmıştır. Bu amaçlara ulaşabilmek için karma yöntemlerden biri olan keşfedici sıralı desen kullanılmıştır. Bu desende, nicel araştırmada kullanılacak değişkenler ve geliştirilmesi planlanan Ahlâkî Konfor Ölçeğine girecek yargıların belirlenmesi için nitel bir aşama; sonra ise değişkenlerle ölçeğin geçerlilik ve güvenirlik tespiti için nicel aşama (Açıklayıcı Faktör Analizi ve Yapısal Eşitlik Modeli) izlenmiştir. Hem nitel hem de nicel araştırmanın pilot uygulamaları Isparta ilinde; nitel araştırma Antalya ilinde; iki aşamalı nicel araştırma ise İstanbul ilinde görev yapan klinisyen veteriner hekimlerle görüşmeler yapılarak gerçekleştirilmiştir. Çalışma ile, klinisyen veteriner hekimlerin ahlâkî konfor düzeylerini ölçme konusunda yeterli geçerlik ve güvenirliğe sahip, 'öz farkındalık', 'öz güven' ve 'tahammülsüzlük' olmak üzere üç boyuttan oluşan 12 maddelik Ahlâkî Konfor Ölçeği geliştirilmiştir. Ayrıca geliştirilen ölçeğin demografik değişkenlerle olan ilişkisi analiz edilerek Ahlâkî Konfor Ölçeği'nin ilk uygulama sonuçları elde edilmiştir. Sonuçlara göre, klinisyenlerin yaşı arttıkça ahlâkî konfor ve öz farkındalık düzeyinin arttığı (p<0.05) görülmüştür. Cinsiyet ve medeni durum değişkenleri açısından, erkek klinisyenlerin kadınlara (p<0.01); evli klinisyenlerin bekârlara (p<0.05) kıyasla daha yüksek ahlâkî konfora sahip oldukları belirlenmiştir. Etik danışmaya ihtiyaç duymayan klinisyenlerin etik danışmaya ihtiyaç duyanlara (p<0.05); iş yeri sahibi klinisyenlerin ücretli çalışanlara (p<0.05) kıyasla daha yüksek ahlâkî konfor, öz farkındalık ve öz güvene sahip oldukları tespit edilmiştir. Öncelikle kendini mesleğe karşı sorumlu hisseden klinisyenlerin diğer gruplara (p<0.05) kıyasla daha yüksek ahlâkî konfor, öz farkındalık ve tahammülsüzlük düzeyine sahip olduğu belirlenmiştir. Sonuç olarak, geliştirilen Ahlâkî Konfor Ölçeği'nin, klinisyen veteriner hekimlerin ahlâkî konfor düzeylerini ölçmede kullanılabilecek geçerli ve güvenilir bir araç olduğu ileri sürülebilir.

The ethical decision-making process is a multidimensional and complex process that begins when veterinarians encounter an ethical problems. It is known that the increase in ethical problems experienced with increasing technology in recent years and the ethical issues inherent in the profession have negative effects on the mental health of veterinarians and the reputation of the profession. The main reason for this situation is that although there are generally accepted diagnostic and treatment standards in the cases encountered by veterinarians in their professional practices, there is no similar acceptance in ethical cases. This study was conducted to understand how clinician veterinarians follow in the decision-making process regarding the solution of ethical problems encountered during their professional practices; to revealing the factors that are effective in this process; and to develop a reliable and valid measurement tool that can be used to determine the level of moral comfort in solution of ethical problems. In order to achieve these aims, exploratory sequential design, one of the mixed methods, was used. In this design, a qualitative phase was followed to determine the variables to be used in the quantitative research and the judgments that will be included in the Moral Comfort Scale to be developed, and then a the quantitative phase (Explanatory Factor Analysis and Structural Equation Model) was followed to determine the validity and reliability of the variables and the scale. Pilot applications of both qualitative and quantitative research were conducted in Isparta province; qualitative research was conducted in Antalya province; The two-stage quantitative research was conducted by interviewing clinician veterinarians working in İstanbul. With this study, a 12-item Moral Comfort Scale consisting of three dimensions: 'self-awareness', 'self-confidence' and 'intolerance', which has sufficient validity and reliability to measure the moral comfort levels of clinician veterinarians, was developed. In addition, the first application results of the Moral Comfort Scale were obtained by analyzing the relationship of the developed scale with demographic variables. According to the results, as the age of the clinicians increased, their moral comfort and self-awareness levels increased (p<0.05). In terms of gender and marital status variables, it was determined that male clinicians had higher moral comfort compared to women (p<0.01) and married clinicians had higher moral comfort compared to single clinicians (p<0.05). It was found that clinicians who did not need ethical counselling had higher moral comfort, self-awareness and self-confidence compared to those who needed ethical counselling (p<0.05) and clinicians who owned a workplace had higher moral comfort, self-awareness and self-confidence compared to paid employees (p<0.05). First of all, it was determined that clinicians who felt responsible towards the profession had higher levels of moral comfort, self-awareness and intolerance compared to other groups (p < 0.05). As a result, it can be claimed that the developed Moral Comfort Scale is a valid and reliable tool that can be used to measure the moral comfort levels of clinician veterinarians.
An applied research on the ethical decision making process in clinician veterinary medicine
Keywords: Veteriner Hekimliği